Risk Assessment of Respirable Dust Exposure to Workers in the Mineral Ore Processing Industry - Susanto, Arif; Putro, Edi Karyono; Kusnadi, Saskia Nur Fadhilah; Santoso, Danny Rosalinawati Mak'dika; Manuel, Anthony Androful (The Indonesian Journal of Occupational Safety and Health, 2024)
Introduction: The mineral ore processing industry is a sector that can generate pollutants in the form of dust during the production, commonly known as respirable dust. This dust can enter the upper respiratory tract and lungs, thereby causing health problems to employees working in the mineral ore processing industry. This study aims to investigate health risks associated with exposure to dust in the mineral ore processing industry. Methods: Environmental Health Risk Analysis (EHRA) was used to assess dust exposure over the previous three years, following the NIOSH Manual of Analytical Methods (NMAM) 0600 for dust sampling measurement. Results: Seven locations with high dust emissions were considered for this study. The results of the respirable dust sampling showed that the concentrations in the previous three years ranged from 1,823 to 6,109 mg/m3, followed by a decrease in the following year to 0.049 to 2,715 mg/m3. Meanwhile, in the final year, the concentration of respirable dust ranged from 0.094 to 1.341 mg/m3. The calculated risk quotient (RQ) value for the previous three years remained below 1, indicating safety. Conclusion: Athough respirable dust was considered safe in the previous year, it is important to constantly control exposure due to continued high levels and the possibility of future increases